Cytochrome P450 1A1: is it involved in disruption of thyroid hormone action by polychlorinated biphenyl?. Issue 5 (September 2011) - Koibuchi, Noriyuki
Evaluation of: Giera S, Bansal R, Ortiz-Toro TM, Taub DG, Zoeller RT. Individual polychlorinated biphenyl (PCB) congeners produce tissue- and gene-specific effects on thyroid hormone signaling during development. Endocrinology 152(7), 2909–2919 (2011). Previous studies have shown that the adverse effects of polychlorinated biphenyl (PCB) exposure may be partly induced by disrupting the thyroid hormone system. In the recent article by Giera et al., the effect of specific PCB congeners on the expression of several thyroid hormone-sensitive genes in various organs was studied using developing rats. The addition of PCB126 significantly augmented cytochrome P450 (CYP)1A1 expression induced by other PCBs. The expression of several genes was also augmented by PCB126, particularly in the liver. These results indicate the involvement of CYP1A1 in PCB-mediated hepatotoxicity. However, this study may not prove directly whether such an effect is exerted though the thyroid hormone system. Further study may be required for clarification.